Carbon nanotube-Yttrium iron garnet nanohybrid synthesized via chemical vapor deposition and its potential application in fabricated screen-printed patch antenna - Hasan, Intan Helina; Ismail, Ismayadi; Hamidon, Mohd Nizar; Mustaffa, Muhammad Syazwan; Abdullah, Nor Hapishah; Shafiee, Farah Nabilah (Elsevier, 2024)
Carbon nanotube-Yttrium iron garnet (CNT-YIG) nanohybrid has been successfully synthesized using chemical vapor deposition (CVD) with yttrium iron garnet (YIG) nanopowders as catalyst, ethanol as carbon stock, and argon as carrier gas. Carbon nanotube (CNT) was observed to have grown from the YIG nanopowders with bamboo-like structures of CNT at a synthesis temperature of 900 °C. FESEM and RAMAN characterization indicated that the CNT-YIG nanohybrid exhibited the growth of bamboo-like CNT with high graphitization. Further analysis of electrical properties showed that the CNT-YIG nanohybrid has exhibited conductivity due to the CNT growth. The nanohybrid in the form of powders was then mixed with an organic vehicle to produce thick film paste and screen-printed onto a substrate as the working material for patch antenna application. Initial measurements using VNA indicated that CNT-YIG nanohybrid gave significant results regarding return loss and bandwidth, proving that the materials could have great potential to enhance patch antenna performance due to their combined electrical and magnetic properties. © 2024 The Authors